2022
DOI: 10.3390/jcm11236935
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curves in Pediatric Robot-Assisted Pyeloplasty: A Systematic Review

Abstract: Background: Robot-assisted surgery demands a specific skillset of surgical knowledge, skills, and attitudes from the robotic surgeon to function as part of the robotic team and for maximal utility of the assistive surgical robot. Subsequently, the learning process of robot-assisted surgery entails new modes of learning. We sought to systematically summarize the published data on pediatric robot-assisted pyeloplasty (pRALP) to decipher the learning process by analyzing learning curves. Methods: This review foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…"Learning curves" originated in industry and has since been applied to many elds, which has led to the widespread use of this term in medical eld [9,10]. Many individual learning curves for a particular procedure are similar, and these curves can be used to guide future training [11].…”
Section: Discussionmentioning
confidence: 99%
“…"Learning curves" originated in industry and has since been applied to many elds, which has led to the widespread use of this term in medical eld [9,10]. Many individual learning curves for a particular procedure are similar, and these curves can be used to guide future training [11].…”
Section: Discussionmentioning
confidence: 99%
“…The consensus published by European Association of Urology (EAU) showed that surgeons could proficiently perform laparoscopic pyeloplasty after implementing the surgery for 50 cases. Niklas Pakkasjärvi ( 46 ) found that surgeons were adept at robotic-assisted laparoscopic pyeloplasty after implementing the surgery for 31 cases. This suggested that surgeon proficiency in both procedures should also be regarded as a risk factor for the prognosis and recurrence of UPJO ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…As revealed in several studies (46)(47)(48)(49)(50)(51)(52)(53), open pyeloplasty, laparoscopic pyeloplasty, and robot-assisted laparoscopic pyeloplasty may generate different curative effects. Meanwhile, the proficiency of surgeons was also one of the factors affecting the curative effects.…”
Section: Discussionmentioning
confidence: 99%
“…To excel in the dynamic field of robotic-assisted surgery, surgeons and nurses can benefit from specialized courses and workshops designed to enhance their skills and proficiency [ 33 ]. Comprehensive training programs often cover various aspects, including system operation, instrument manipulation, and troubleshooting, ensuring healthcare professionals are well equipped to navigate the intricacies of robotic platforms [ 23 , 34 ].…”
Section: Costs Maintenance and Feasibility Of Robotic-assisted Surgic...mentioning
confidence: 99%